Bottom ash limbah batubara sebagai media filter yang efektif pada pengolahan limbah cair tekstil - Ainur Rosyida (Jurnal Rekayasa Proses, 2011)
Wastewater from textile industry contains very high contaminants. Therefore, a suitable treatment method is highly required to fulfill wastewater quality standard. Filtration is a step in wastewater treatment which affects duration of the whole process. By filtration, organic materials, solid particles and heavy metals can be significantly reduced. As a result, the load for biological process (activated sludge) decreases very much. The objective of this research is to obtain the most effective filtration medium for wastewater treatment from textile industry. Performance of three filter media (activated carbon, activated zeolite and coal bottom ash) were compared. The experiment was started by doing a preliminary process (stabilization, flotation, coagulation- sedimentation) to separate big size particles from wastewater before filtration. Then, the filtration medium was placed in a filtration column and a stream of wastewater was flown through the column at a certain flow rate. In order to better understand the effectiveness of medium, a sample of wastewater before and after filtration was measured for TSS, BOD, COD values and heavy metal (Cr) content. The experimental result showed that filtration using coal bottom ash was more effective than that using activated zeolite and activated carbon. The filtration was able to reduce TSS by 32,5%, COD by 54,1%, BOD by 58,9% and heavy metal (Cr) content 80,8%. Thus, coal bottom ash could be utilized as an effective filtration medium in the treatment of textile industry wastewater.